ISOLASI DAN IDENTIFIKASI SENYAWA SITOTOKSIK DAUN NAGASARI (Calophyllum nagassarium Burm.f.) TERHADAP LARVA Artemia salina Leach - I Wayan Pramana Eka Putra; Sri Rahayu Santi; Ni Luh Rustini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
Calophyllum nagassarium Burm.f. or nagasari is a kind of plant that often be used as medical plant such as for antiseptic, laxative, blood purifier, helminthic, and tonic. This study aimed to isolate and identify cytotoxic compounds of nagasari leaves by extracting 1000 g of leaf powder with 10 L of 96% ethanol (5L x 2) to produce 66.81 g of ethanol extract (LC50 = 19.06 ppm). Fractionation of the ethanol-water extract (7: 3) in a row with 300 mL of n-hexane, chloroform 400 mL, 400 mL of n-butanol, and water and toxicity tests against larvae of Artemia salina Leach generate 2.52 g of n-hexane extracts (LC50 = 275.42 ppm), 7.06 g chloroform extract (LC50 = 63.10 ppm), 9.54 g of n-butanol extract (LC50 = 27.54 ppm) and 25.38 g aqueous extract (LC50 = 478 , 63 ppm). N-buthanol extract which was the most toxic was then separated, purified and identified. The separation of 2.0 g of n-butanol extract using column chromatography techniques with silica gel 60 as the stationary phase and chloroform- n-butanol (5: 3) as the mobile phase resulted in 5 fractions (F1, F2, F3, F4, and F5). Fraction F1 which was the most toxic (LC50 = 91.20 ppm) was then separated by preparative Thin Layer Chromatography and resulted two fractions (FA and FB). Fraction FB was the most toxic with LC50 = 83.18 ppm. UV-Vis and IR spectrophotometric analysis of FB identified a compound suspected to be terpenoides that has the characteristics of functional groups such as O-H, O = C-OH, aliphatic C-H.